Self-Regulation of Learning in Higher Education Mobile Learning Landscape: A Review - Chi, Nguyen Yen; Huyen, Nguyen Thi (VNU Journal of Science: Education Research; Vol 41 No 4DO - 10.25073/2588-1159/vnuer.5207, 2025)
Mobile learning has emerged as a convenient means of learning anytime anywhere in the busy world today. Previous reviews have investigated the use of mobile learning in higher education or mobile self-regulated learning interventions throughout all levels of education; however, no review has been conducted to associate mobile learning and self-regulated learning specifically at higher education level. This study adopted a systematic literature review from the Scopus database, comprising 16 articles selected for bibliometric and content analysis. Results show that only a few attempts have been made to investigate self-regulated learning in mobile environments in a systematic manner. Almost all results report positive outcomes regarding the impact of mobile learning on self-regulated learning and of mobile self-regulated learning on learning outcomes. However, the potential of mobile learning interventions has been largely untapped, and this review also calls for research into pedagogy and assessment in mobile learning. More robust theories in the topic will provide insights for designing instruction and relevant tools to enhance the experience and effectiveness of mobile learning.